3D‐Enhanced, High‐Performing, Super‐hydrophobic and Electromagnetic‐Interference Shielding Fabrics Based on Silver Paint and Their Use in Antibacterial Applications. Issue 40 (5th November 2019) - Ghosh, Sabyasachi; Das, Poushali; Ganguly, Sayan; Remanan, Sanjay; Das, Tushar Kanti; Bhattacharyya, Swarup Krishna; Baral, Joydeep; Das, Amit Kumar; Laha, Tapas; Das, Narayan Ch.
Abstract: A unique brush coating technique was adopted to prepare high microwave absorbing super‐hydrophobic bactericidal fabrics. 3D micro‐CT, field emission scanning electron microscopy (FE‐SEM) and high resolution transmission electron microscopy (HR‐TEM) analyses were employed to establish the composite morphology. X‐ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) were used to characterize the embedded silver nanoparticles in the cotton fabrics. The developed thin wearable coated fabrics hold the lowest resistivity of 8 ohm‐cm −2 (lighten up series of LEDs) and electromagnetic interference (EMI) shielding effectiveness (SE) of 30.07 dB at 0.3 mm coating thickness within the X‐band frequency range. These thin coated fabrics can be the used in the flexible electronic devices along with extreme bactericidal feature against E. coli . Abstract : Our recent approach of coated textile fabrication has been accomplished by means of exclusive brush coating technique using industrial based silver paint. The fabric was characterized by both 2D and 3D morphological analysis for developing potentially high EMI shielding materials. Side by side, the thin, wearable and super‐hydrophobic brush coated fabric was capable enough to lighten up the series of LEDs and also performed antibacterial property via destroying the cell membrane with blocking the respiratory system of the E. coli bacteria.